Comparison of transformation frequencies among selected Streptococcus pneumoniae serotypes - Joloba, Moses L.; Kidenya, Benson R.; Kateete, David P.; Katabazi, Fred A.; Muwanguzi, Julian K.; Asiimwe, Benon B.; Alarakol, Simon P.; Nakavuma, Jessica L.; Bajaksouzian, Saralee; Windau, Anne; Jacobs, Michael R. (International journal of antimicrobial agents, 2010)
Although there are over 90 serotypes of Streptococcus pneumoniae, antimicrobial resistance is predominantly found in a limited number of serotypes/serogroups, namely 6, 9, 14, 19 and 23. There is no compelling mechanism to account for this restriction. We aimed to determine whether serotypes commonly associated with drug resistance have higher transformation frequencies than those that are susceptible to antimicrobial agents. An in vitro investigation of the genetic transformation frequency of drug-resistant serotypes compared with that of susceptible serotypes under the influence of synthetic competence-stimulating peptides was performed. The transforming DNA was genomic DNA carrying a Tn916-like transposon containing the mefE gene that confers resistance to erythromycin. It was observed that serotypes 6, 9, 14, 19 and 23, which are highly associated with drug resistance, do not exhibit a higher degree of transformation efficiency than other serotypes. These findings suggest that the association of serotype with drug resistance is likely due to prolonged exposure to transforming DNA resulting from longer nasopharyngeal carriage and to a greater selective pressure from antimicrobials, particularly in children. This is the first study to compare the transformation frequencies of pneumococcal clinical isolates using genomic DNA that carries the composite Tn916-like element.
Keywords: Streptococcus; pneumoniae; Drug-resistant serotypes serogroups